Autonomy in cardiac patients: A concept analysis - Madia Yuni Ardani; Sidik Awaludin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Autonomy is a crucial aspect of cardiac patient care, which involves complex medical decisions and necessitates the patient's active participation. The appropriate application of the principles of autonomy can enhance the quality of care and patient satisfaction in managing chronic heart disease. Purpose: To refine the concept of autonomy, analyze it in depth, and formulate an operational definition. Methods: The analysis approach is based on the Avant concept, which was obtained from online databases namely Science Direct, PubMed, and Google Scholar using keywords “Autonomy Concept” AND “Heart”. Results: The concept analysis identified key attributes, including independent decision-making, independence, freedom, and the ability to think logically. Conclusion: The analysis reveals that the independence of heart patients is influenced by their understanding of their health status, the role of their family, and the role of medical personnel in providing accurate and precise information.